TRANSPARANSI DAN AKUNTABILITAS PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA - Kumalasari, Deti; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to find out the implementation of Transparency and Accountability principles of District / Village Government in the management of Village Fund Allocation which includes activities i.e.: planning, implementation, report and responsibility of Village Allocation Fund. The research method has been carried out by using qualitative method and descriptive approach. The informant consists of village head, village secretary, village treasury, vice chairman of BPD, and representative of the community. The data collection technique has been conducted by using interview and documentary. The data analysis technique has been started by organizing the data, simplifying the data, processing the data analysis, and interpreting the result. The result of the research shows that the village government of Bomo Village Rogojampi District of Banyuwangi has implemented the transparency and accountability principles in the management of Village Fund Allocation (ADD). The implementation and the planning of village fund allocation has implemented the transparency and accountability principles. Meanwhile, the responsibility of village allocation fund physically has shown the transparent and accountable implementation, but from the administration point of view some improvements are needed for further development, because it has not completely complied with requirements of laws and regulations.Keywords: Management village fund allocation (add), transparancy, accountability.